Some remarks on the semantics of ir + Infinitive in European Portuguese - Cunha, Luis Filipe (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This paper deals with the semantics of the European Portuguese structure ir + Infinitive, in particular when it occurs with the Pret©rito Perfeito (a terminative past tense) and the Presente do Indicativo (Simple Present). We will argue for the hypothesis that, indeed, in this language there are two different semantic configurations behind the ir + Infinitive sequence. In fact, we will begin describing a first reading in which ir seems to retain most of its basic lexical properties, imposing strong restrictions to the situations that can combine with it, concerning particularly their aspectual profile and the presence or absence of the agentive feature; then, we will explore a second interpretation in which ir behaves like a pure temporal operator of futurity, exhibiting the characteristics of a semi-auxiliary and imposing no relevant constraints to the eventualities that co-occur in the whole structure.